HUMAN RIGHTS IN INTERNATIONAL RELATIONS: BETWEEN UNIVERSALITY AND POLITICIZATION - Bilousov, Oleksandr; Kryvdina, Inna (Current Problems of Sustainable Development, 2026)
Human rights today are not only a moral category, but also a legally binding international standard. Human rights as a fundamental legal and political category are the result of the long historical development of human civilization. The modern understanding of human rights was not formed instantly, but became the result of centuries-old development of philosophical thought, political struggle and evolution of legal systems. The idea that a person has certain inalienable rights that belong to him from birth and cannot be arbitrarily taken away by the state was gradually formed in different historical eras, passing a difficult path from moral and philosophical concepts to legally enshrined international standards. The article examines the role of human rights in the modern system of international relations through the prism of the correlation of their universal nature and political use. The evolution of the concept of human rights after World War II, its consolidation in international legal acts and transformation into an important tool of global governance are revealed. The normative basis for the universality of human rights is analyzed, in particular the provisions of the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights and the European Convention on Human Rights. Particular attention is paid to the problem of politicization of human rights, which is manifested in the selective application of international standards, the use of dual approaches and the instrumentalization of human rights in the foreign policy of states. The impact of politicization on the effectiveness of international mechanisms for the protection of human rights, in particular the activities of international organizations and judicial institutions, is studied. It is substantiated that politicization not only undermines trust in the international system for the protection of human rights, but also complicates the implementation of the principle of universality. At the same time, it is proven that complete depoliticization of human rights is impossible, since they are integrated into the sphere of international politics and security. The conclusion is made about the need to ensure a balance between the universality of human rights and their political dimension by strengthening the independence of international institutions, unifying approaches to assessing violations, and increasing the role of international law in regulating interstate relations.